LncRNA FENDRR Inhibits ox-LDL Induced Mitochondrial Energy Metabolism Disorder in Aortic Endothelial Cells via miR-18a-5p/PGC-1α Signaling Pathway - Wang, Guiming; Yang, Yudong; Ma, Honggang; Shi, Liuming; Jia, Wenbin; Hao, Xing; Liu, Weizong (Frontiers in Endocrinology, 2021)
Atherosclerosis (AS) is the main cause of morbidity and mortality in the world. Mitochondrial dysfunction is closely related to the AS. At present, several signaling pathways related to mitochondrial dysfunction have been found, one of which is around PGC-1α. PGC-1α is a transcription activator, which is related to mitochondrial biogenesis and antioxidant defense. In this study, we explored the effect of miR-18a-5p/PGC-1α signaling pathway on mitochondrial energy metabolism in HAECs with ox-LDL treatment. The results showed that the mitochondrial energy metabolism disorder in HAECs treated by ox-LDL was related to the down regulation of LncRNA FENDRR and PGC-1α. FENDRR could reverse ox-LDL induced mitochondrial energy metabolism disorder and up regulate the PGC-1α expression. FENDRR could be used as ceRNA to inhibit the miR-18a-5p expression and reduce the negative regulation of miR-18a-5p on PGC-1α. Down regulation of miR-18a-5p expression or up regulation of PGC-1α in ox-LDL treated HAECs could reverse mitochondrial energy metabolism disorder. In conclusion, these findings suggested that FENDRR/miR-18a-5p/PGC-1α signaling pathway regulated mitochondrial energy metabolism in HAECs, ox-LDL down regulated the expression of PGC-1α and cause mitochondrial energy metabolism disorder by inhibiting this signal pathway.